Peran Psikologi Manajemen dalam Meningkatkan Mutu Lembaga Pendidikan melalui Kinerja Pendidik - Umi Nur Khamidah; Putri Nur Fadhila; Dian Eka Puspitasari; Mualimin Mualimin (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study examines the strategic role of management psychology in enhancing educational institution quality through optimizing teacher performance. Employing a qualitative descriptive approach via library research—analyzing recent journals, books, and sources from 2021–2026—data were processed using content analysis techniques, encompassing systematic identification, categorization, and interpretation of prior findings to reveal patterns, relationships, and research gaps. Results indicate that psychological factors such as work motivation, mental well-being, supportive leadership, and conducive work climate significantly shape teachers' behaviors and performance, fostering effective and sustainable learning environments. Integrating management psychology principles proves essential for holistic human resource management in education, offering practical implications for school leaders' policies to build high-quality educational systems. In addition, the study emphasizes that consistent professional development and emotional support systems for teachers further strengthen institutional effectiveness and improve instructional outcomes. Therefore, management psychology serves as a fundamental framework in aligning organizational goals with teacher well-being and performance enhancement in educational settings.